Mental Coaching for Emotional Management in High-Risk Correctional Institutions with Super Maximum Security - Kaumpungan, Pisonya Mahardika (Journal of Mental Health and Social Rehabilitation, 2024)
Mental coaching such as emotional management training in Correctional Institutions (prisons) is not only for training purpose but also should be a mandatory treatment for inmates. This coaching is useful for maintaining the mental health of inmates when serving their sentences, a form of rehabilitation, and preparation for integration. However, this form of coaching faces obstacles to being applied to high-risk inmates who are held in super maximum security prisons. Through visits and interviews with officers, it can be seen that this mental coaching training will be more beneficial for prison officers, especially super maximum prison security officers who face securing high-risk inmates every day.